Urban indoor-outdoor aerosol measurements in Portugal and the global warming scenario - Miguel, A. F. (2012)
Aerosols play a major role both in climate change and air quality. They affect climate by interfering with radiative transfer and the atmospheric temperature. Aerosol particulate matter has also been associated with various adverse health effects. Aerosol particles’ number and size distributions were measured inside and outside the houses in the urban areas of Évora and Lisbon, in Portugal. The impact of the occurrence of a residential fire in the aerosols’ particle number is evaluated and discussed. Finally, we consider how the global increase in temperature can affect the concentration of aerosols in the atmosphere via increased boundary layer convection.